Effect of SiO2, ZrO2, and SiO2-ZrO2 Supports on Product Distribution in Glucose Hydrogenolysis over Cu-Ni-WOx Catalysts - Ahmad Sholeh Romdlon; Yuniar Ponco Prananto; Siti Mariyah Ulfa (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Biomass-derived glucose is an important platform molecule to produce value-added oxygenated chemicals through catalytic conversion. In this study, Cu-Ni-WOx catalysts supported on SiO2, ZrO2, and SiO2-ZrO2 were prepared by wet impregnation and evaluated for the hydrogenolysis of glucose in water. The catalysts were characterized by X-ray diffraction, SEM-EDX, and pyridine-adsorption FTIR to examine the relationship between catalyst structure, acidity, and catalytic behavior. Catalytic tests were carried out in a batch reactor at 300 °C under 2 MPa H2 for 2 h. All catalysts showed comparable glucose conversion in the range of 92.2-93.1%, whereas the support strongly influenced the distribution of liquid products. The SiO2-supported catalyst favored glycol/glycol-like compounds and cyclic ether/THF products, indicating a stronger tendency toward oxygen-retaining pathways. In contrast, the SiO2-ZrO2-supported catalyst showed higher distribution toward cyclic ketones and aliphatic alcohols, while the ZrO2-supported catalyst exhibited an intermediate pattern. These findings suggest that support-dependent acidity plays an important role in directing hydrogenolysis pathways and controlling the relative formation of oxygen-retaining and rearranged products. This work highlights the importance of support composition in tuning the product distribution of Cu-Ni-WOx catalysts for glucose valorization into value-added oxygenates. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).